ON THE FLOW PAST RECTANGULAR CYLINDERS: PHYSICAL ASPECTS AND NUMERICAL SIMULATION - Almeida, O.; Mansur, S. S.; Silveira-Neto, A. (Revista de Engenharia Térmica, 2008)
This paper concerns with unsteady incompressible flows around rectangular cylinders with side ratio varying from 1 to 10. Phenomenological aspects are discussed and numerical simulations are performed using a SIMPLEC finite volume code. A third-order QUICK scheme is employed for the advective terms in the Navier-Stokes equations, while a second-order fully implicit method is used for the time discretization. For validation purpose, preliminary simulations are carried out at Re = 300. Afterwards, the flow patterns and the wake periodic features are examined at Re = 1,000, 5,000, and 22,000, for which turbulent effects should not be neglected. In some of those cases, large-eddy simulation (LES) is employed, using the classical sub-grid Smagorinsky model. Important physical mechanisms determining vortex shedding frequency are placed in evidence. The present predictions are compared with numerical and experimental results from other works and a good agreement is reached.